An Ecological Philosophy of Self and World: What Ecocentric Morality Demands of the Universe - Riggio, Adam A. (My University, 2012)
When environmental philosophy began as a political movement, one of its original goals was to transform people's lifestyles. This required appeals to everyday intuitions and emotional writing evoking the intrinsic value of nature. This style exists in institutional environmental philosophy today, but sits uneasy with academic pressure toward rigor and careful analysis. The first half of my thesis criticizes various problems in environmental philosophy regarding these issues and arguments for other moral principles that displace intrinsic value. I attempt to return the concept of intrinsic value to a prominent place in environmental philosophy, not as a popular intuition, but as an answer to one central philosophical question: the point of human existence. Engaging with particular topics in ecology, biology, phenomenology, ethology, complexity theory, and the assemblage theory of Deleuze and Guattari, the second half of my thesis builds a concept of selfhood that I hope is adequate to answer that question of why humanity should bother ensuring its survival.
Keywords: Ethics; Ecology; Environmentalism; Biology; Selfhood; Activism; Biodiversity; Continental Philosophy; Ethics and Political Philosophy; Other Ecology and Evolutionary Biology; Other Psychology; Political Theory; Biodiversity